Prisoner of history : Aspasia of Miletus and her biographical tradition - Henry, Madeleine Mary, 1949- (OUP E-Books., 1995)
According to legend, Aspasia of Miletus was a courtesan, the teacher of Socrates, and the political adviser of her lover Pericles. Next to Sappho and Cleopatra, she is the best known woman of the ancient Mediterranean. Yet continued uncritical reception of her depiction in Attic comedy and naive acceptance of Plutarch's account of her in his Life of Pericles prevent us from understanding who she was and what her contributions to Greek thought may have been. Madeleine Henry combines traditional philological and historical methods of analysis with feminist critical perspectives, in order to trac.